(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
: Hyperemesis Gravidarum (HEG) is a pregnancy illness of long-term nausea and vomiting with weight loss, dehydration, and malnutrition that is potentially life-threatening to mother and baby. In 2013, the Ministry of Health of the Republic of Indonesia stated that 14.8% of 5,212,568 pregnant women experienced HEG. HEG is influenced by various factors, including physical activity and stress levels. The intensity of physical activity during pregnancy directly impacts maternal health. Conversely, stress disrupts the hormonal balance in the body. Therefore, this study analyzed the relationship between physical activity, stress levels, and the severity of HEG at Tugurejo Hospital and Roemani Hospital in Semarang. This type of research is an analytic observation with a cross-sectional approach. The study population was HEG patients at Tugurejo Hospital and Roemani Hospital who met the inclusion criteria totaling 45 people with total sampling, tested with Spearman Rank. The correlation test results showed that physical activity with HEG degree had a weak correlation coefficient (r) of 0.311 positive correlation direction with ρ-value 0.037 (ρ<0.05), and stress level with HEG degree had a weak correlation coefficient (r) of 0.398 positive correlation direction with ρ-value 0.007 (ρ<0.05). A significant relationship exists between physical activity and stress level and the degree of HEG in Tugurejo Hospital and Roemani Hospital Semarang. In conclusion, the higher the physical activity performed and the higher the level of stress experienced, the more severe the degree of HEG.